Poly-Trauma Rehabilitation Center adaptive healing for Poly-Trauma victims - Pervera, Van Joseph B.
The burden of injuries and disabilities on the Philippines’ society and its economy should not be understated, especially for a country that depends largely on its labor force. A large portion of these cases are brought about by Poly-Trauma. Overcrowding and lack of safety practices worsen this burden. In the current situation of hard living conditions, incidence of accidents resulting in Poly-trauma may be expected to rise. Although there are health facilities that cater to trauma cases, these facilities fail to provide continuous treatment that allows Poly-Trauma victims to return to the level of independence they previously had in their lives. This study proposes a project that provides the continuation of treatment that precedent institutions fail to provide. The treatment process that Poly-Trauma Victims undergo is analyzed and their various needs are identified. Professionals with expertise on the subject are consulted and further insight is asked. To conclude, a simplified treatment process is formulated with the purpose of making it a basis for access restriction and general circulation. User-specific exclusivity is enforced on certain spaces while overlapping areas are provided for interaction. Provisions for necessary services from allied health professions and therapeutic activities are identified and properly laid out with the goal of minimizing user traffic in key areas. Independence in lifestyle with close observation is promoted through provision of independent living spaces allowing certain freedoms while ensuring that lifestyle changes are not met with hostility. Amid rising living costs compounded with the additional costs brought by their conditions, self-sufficiency is encouraged by providing spaces for livelihood training. Using courtyards bring focus on open space and the benefits it brings to Poly-Trauma victims, giving privacy but not without means of engaging adjacent open spaces. The end goal of reintegration to the community is done systematically with the use of courtyards and open spaces with controlled public access.